1994
DOI: 10.1192/bjp.164.6.802
|View full text |Cite
|
Sign up to set email alerts
|

Nefazodone and Imipramine in Major Depression: A Placebo-Controlled Trial

Abstract: Nefazodone is a phenylpiperazine antidepressant with 5-HT2 antagonism and 5-HT reuptake inhibition. Two hundred and eighty-three out-patients with a diagnosis of DSM-III-R major depression of at least one-month duration (65% ill for over 6 months), and a mean score of 24 on the 17-item Hamilton Rating Scale for Depression (HRSD), were randomised to treatment with nefazodone, imipramine, or placebo. The double-blind treatment period was 8 weeks in duration. Nefazodone's antidepressant efficacy was comparable wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Several studies comparing NEF with imipramine found equal efficacy [9][10][11][12]; the same holds true for another study versus AMI [13].…”
Section: Introductionmentioning
confidence: 61%
“…Several studies comparing NEF with imipramine found equal efficacy [9][10][11][12]; the same holds true for another study versus AMI [13].…”
Section: Introductionmentioning
confidence: 61%
“…However, antidepressants such as nefazodone or trazodone, which are potent drugs to reduce clinical symptoms in depression [32,60,62,[75][76][77], but increase REM sleep (nefazodone) or have only little effect on REM sleep variables (trazodone), cast doubts on this theory. Whether or not nefazodone as well as trazodone, which are both associated with a more pronounced improvement in objective and subjective sleep variables compared to SSRIs, are able to provide clinical antidepressant benefits without objective sleep disturbances, has to be explored in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…Like trazodone it has modest 5-HT reuptake blocking properties (Table 1) and is metabolised to the 5-HT receptor agonist, m-CPP. Controlled trials in patients with major depression have shown that in doses of 400 mg and greater nefazodone are more effective than placebo and generally equal in therapeutic activity to comparator drugs 6 ; these studies, however, have focused on outpatients with moderate depressive disorders. Nefazodone is usually given in two divided doses starting at 200 mg daily with titration to 400 mg daily after about a week.…”
Section: Nefozodonementioning
confidence: 99%
“…Nefazodone is generally well tolerated with the most common side effects being headache, loss of energy, dizziness, dry mouth, nausea and somnolence 6 . It appears less cardiotoxic than tricyclic antidepressants and is probably safer in overdose.…”
Section: Nefozodonementioning
confidence: 99%